Proses Penjualan dan Sistem Kerja Tenant pada Event Picnic Festival oleh PergiKuliner - Ulfah, Nabilah; Syah, Firman (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2024)
A culinary festival is an event that presents various types of food and drinks from various sellers, from street vendors to restaurants in one place over a certain period of time. Research on this culinary festival focuses on understanding the flow of booth sales in an effort to achieve booth targets at the Picnic Festival event and identifying the work system of tenants at the Picnic Festival event. To achieve a comprehensive understanding regarding sales flow and tenant work systems, research was carried out using interview, observation and documentation methods. The results of this research show that at the Picnic Festival event, the booth sales flow in an effort to achieve the target begins with the approaching stage, filling in the form, and admin payment. Meanwhile, the tenant work system during the Picnic Festival event uses a revenue sharing system and ordering sponsored products.